Reduction in mydriatic drop size in premature infants. - Wheatcroft, S (1993)
In a prospective study of 26 premature infants, 5 microliters microdrops were compared with standard 26 microliters eye drops of cyclopentolate 0.5% and phenylephrine 2.5%. There was no statistical difference in pupil dilatation. The 5 microliters microdrops have potentially fewer adverse effects in premature infants.